Strategi dan Kebijakan Penegakan Hukum Tindak Pidana Pencucian Uang dari Tindak Pidana Asal di Bidang Perikanan - Syakur, Syahrijal (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2023)
Law enforcement on money laundering originating from criminal acts in the field of fisheries (Illegal Fishing) after the Constitutional Court Decision Number 15/PUU-XIX/2021, which is not only the duty of investigators in the field of fisheries, but also the public prosecutor and judges in court who will process the results investigation at trial level. For this reason, each of these law enforcement officers must have the same perception in law enforcement as stipulated in the laws and regulations in the field of fisheries. This paper aims to find out the investigation of money laundering where the predicate crime is in the field of fisheries related to the differences in the respective procedural law and to find out the authority of the Special Fisheries Court to adjudicate money laundering cases where the predicate crime is in the fishery sector. This research used normative or doctrinal methods. The recommendation from the author is that the investigation of money laundering cases where the predicate crime is in the field of fisheries is carried out by separating the case files of criminal acts in the field of fisheries from the files of investigations of money laundering crimes but the investigation is still carried out in parallel. Regarding the authority of the special court for fisheries, judges at the special court for fisheries can interpret the law to mean that based on Article 71 of the Fisheries Law, the special court for fisheries has the authority to examine, adjudicate, and decide on money laundering cases where the predicate crime is in the field of fisheries.